ANALISIS TEOLOGI PASTORAL KHOTBAH DALAM KITAB KISAH PARA RASUL: SUATU IMPLIKASI BAGI HAMBA TUHAN - Jonidius Illu; Eliyunus Gulo; Jumadi Jumadi; Albinus Nainggolan (Manna Rafflesia, 2026)
This article arises from a pastoral concern regarding the need for sermons that are not only theologically informative but also pastorally edifying in the light of the Gospel of Jesus Christ. Employing an exegetical and pastoral theological approach, this study analyzes several key sermons in the book of Acts—particularly those delivered by Peter (Acts 2), Stephen (Acts 7), and Paul (Acts 13 and 17)—to explore principles of effective Gospel communication for today’s ministers. The findings reveal that apostolic preaching emphasized not only doctrinal teaching but also served as a pastoral act characterized by boldness, contextual sensitivity, and a call to repentance and confession of faith in Jesus as Lord and Savior. The main conclusion of this study is that preaching in the context of Acts functions as a means of grace that strengthens faith, renews life, and equips the church to follow Christ. The novelty of this article lies in its integrative emphasis on the homiletical and pastoral dimensions of apostolic preaching and its relevance for ministers today who long to serve faithfully to the Gospel with sensitivity to the needs of souls.